About the tensile mechanical behaviour of carbon fibers fabrics reinforced thermoplastic composites under very high temperature conditions. (15th January 2020) - Carpier, Y.; Vieille, B.; Coppalle, A.; Barbe, F.
Abstract: The present work focuses on the thermomechanical behaviour of thermoplastic-based composite materials subjected to the combined action of a mechanical loading in tension and homogeneous temperature conditions. The investigations on the relationship between local temperature resulting from the local atmosphere and the mass losses are essential in understanding the influence of fire on the thermo-mechanical behaviours of polymers and polymer matrix composites. Regardless the testing atmosphere, the decomposition onset temperature is about 500 °C. From isothermal tensile tests conducted at temperatures ranging from ambient to 520 °C, it appears that the retention of the axial stiffness of quasi-isotropic carbon fibers reinforced polyphenylene sulfide (PPS) laminates is relatively high (about 70% of its initial value) beyond the decomposition temperature. At the same time, the ultimate strength dramatically decreases (about 25% of its initial value). The obtained results also show that melting is instrumental to rule the tensile behaviour of quasi-isotropic C/PPS laminates. Conversely, matrix melting significantly influences the damage mechanisms within the laminate. Finally, for testing temperatures close to the onset decomposition temperature, porosities appear and grow within the laminates, ultimately contributing to the degradation of the mechanical properties.